Use of intraoperative luminescent methods for detecting affected lymph nodes in patients with complicated forms of colon cancer - M. A. Kubrak; S. M. Zavhorodnii; M. B. Danyliuk; A. I. Rylov (Сучасні медичні технології)
The issue of the volume of lymphatic dissection in patients with complicated forms of colon cancer and the possibility of using methods of intraoperative visualisation of the affected lymph nodes remains controversial.